Non–FDA-Reviewed Imported European Formula Use Among Parents in Urban Pediatric Private Practice. (June 2020) - Du, Nan; DiMaggio, Dina M.; Williams, Jamila K.; Leus, Ine; Shabanova, Veronika; Song, Xuemei; Porto, Anthony F.
In 2018, the American Academy of Pediatrics warned consumers over the increasing use of imported infant formulas. The purpose of this study was to assess the usage of imported European infant formula among parents in a large urban private practice. An anonymous survey was distributed at well-child appointments to a convenience sample of parents at an urban private pediatric practice from November 2017 to March 2018. Of the 750 eligible respondents, 552 (74%) completed the survey. Of the parents using formula, 20% were using imported European infant formulas. The most commonly used formula was Holle (33%), and 72% were acquired from web-based third-party vendors. Parents chose to use these formulas because they believed that European formulas contained better ingredients. Only 8% of parents received information about European infant formula from their pediatricians. Pediatricians need to be aware of these formulas and their risks to educate families on the use and safety of these formulas.